Oblikovanje novih urbanih naselij - Venturi, Marco (Urbani izziv, 1998)
Even though at present the attention of European planning agencies is focused on issues of re-use and green areas, a number of events are again raising the need to define proper answers to problems of new urbanization. Following a discussion on the changing definition of the urban phenomenon, the tender for a new settlement in Layenhof near Mainz in Germany and the architectural, urban design solution are presented.
Keywords: mesta; prostorsko planiranje; spatial planning; urbanism; urbanistično planiranje; urbanizem